Positron Emission Tomography Imaging of Staphylococcus aureus Infection Using a Nitro-Prodrug Analog of 2-[(18)F]F-p-Aminobenzoic Acid - Li, Yong (ACS Infect Dis, 2020)
Deep seated bacterial infections caused by pathogens such as Staphylococcus aureus are difficult to diagnose and treat and are thus a major threat to human health. In previous work we demonstrated that positron emission tomography (PET) imaging with 2-[(18)F]F-p-aminobenzoic acid (2-[(18)F]F-PABA) could non-invasively identify, localize and monitor S. aureus infection with excellent sensitivity and specificity in a rodent soft tissue infection model. However, 2-[(18)F]F-PABA is rapidly N-acetylated and eliminated, and in an attempt to improve radiotracer accumulation in bacteria we adopted a pro-drug strategy in which the acid was protected by an ester and the amine was replaced with a nitro group. Metabolite analysis indicated that the nitro group of ethyl 2-[(18)F]fluoro-4-nitrobenzoate (2-[(18)F]F-ENB) is converted to the corresponding amine by bacteria-specific nitroreductases while the ester is hydrolyzed in vivo into the acid. PET/CT imaging of 2-[(18)F]F-ENB and the corresponding acid 2-[(18)F]F-NB in a rat soft tissue infection model demonstrated colocalization of the radiotracer with the bioluminescent signal arising from S. aureus Xen29, and demonstrated that the tracer could differentiate S. aureus infection from sterile inflammation. Significantly, the accumulation of both 2-[(18)F]F-ENB and 2-[(18)F]F-NB at the site of infection was 17-fold higher than at the site of sterile inflammation compared to 8-fold difference observed for 2-[(18)F]F-PABA, supporting the proposal that the active radiotracer in vivo is 2-[(18)F]F-NB. Collectively, these data suggest that 2-[(18)F]F-ENB and 2-[(18)F]F-NB have the potential for translation to humans as a rapid, noninvasive diagnostic tool to identify and localize S. aureus infections.